Anger and Contested Place in the Social World - TenHouten, Warren D. (Scientific Research, 2018)
The root term angr includes in its meaning anger-rage and sadness-grief, which today are recognized as two primary or basic emotions. Anger involves the brain’s “rage system”, an architecture widely represented in the animal kingdom. Anger and its opposite, fear, are the positive and negative adaptive reactions to the existential problem of social hierarchy and associated competition for resources and opportunities. Anger’s valence can be negative insofar as it is unpleasant for all involved but is primarily positive because anger is goal-seeking and approach-oriented. Anger functions to assert social dominance, and detection of anger in others reveals possible challenge intentions. The management and control of anger is linked to impulsivity, patience, and tolerance. While the Russell-Fehr model views emotions such as aggressiveness, sullenness, and resentment as subcategories of anger, we rather contend that anger is an embedded subcategory of secondary- and tertiary-level emotions. We model one such emotion, resentment, as a tertiary emotion. Resentment has anger as its key emotion, and includes the primary emotions disgust and surprise, which can combine in pairs to form outrage, contempt, and shock. A classification of 7 secondary and 21 tertiary emotions in which anger is embedded is presented. We argue that the classification of complex emotions is a potential, and necessary, project for the sociology-anthropology of emotions.
Keywords: Anger; Fear; Sullenness; Emotions Classification; Social Dominance